Properties, Genetics and Innate Immune Function of the Cuticle in Egg-Laying Species - Kulshreshtha, Garima; D’Alba, Liliana; Dunn, Ian C.; Rehault-Godbert, Sophie; Rodriguez-Navarro, Alejandro B.; Hincke, Maxwell T. (Frontiers in Immunology, 2022)
Cleidoic eggs possess very efficient and orchestrated systems to protect the embryo from external microbes until hatch. The cuticle is a proteinaceous layer on the shell surface in many bird and some reptile species. An intact cuticle forms a pore plug to occlude respiratory pores and is an effective physical and chemical barrier against microbial penetration. The interior of the egg is assumed to be normally sterile, while the outer eggshell cuticle hosts microbes. The diversity of the eggshell microbiome is derived from both maternal microbiota and those of the nesting environment. The surface characteristics of the egg, outer moisture layer and the presence of antimicrobial molecules composing the cuticle dictate constituents of the microbial communities on the eggshell surface. The avian cuticle affects eggshell wettability, water vapour conductance and regulates ultraviolet reflectance in various ground-nesting species; moreover, its composition, thickness and degree of coverage are dependent on species, hen age, and physiological stressors. Studies in domestic avian species have demonstrated that changes in the cuticle affect the food safety of eggs with respect to the risk of contamination by bacterial pathogens such as Salmonella and Escherichia coli. Moreover, preventing contamination of internal egg components is crucial to optimize hatching success in bird species. In chickens there is moderate heritability (38%) of cuticle deposition with a potential for genetic improvement. However, much less is known about other bird or reptile cuticles. This review synthesizes current knowledge of eggshell cuticle and provides insight into its evolution in the clade reptilia. The origin, composition and regulation of the eggshell microbiome and the potential function of the cuticle as the first barrier of egg defense are discussed in detail. We evaluate how changes in the cuticle affect the food safety of table eggs and vertical transmission of pathogens in the production chain with respect to the risk of contamination. Thus, this review provides insight into the physiological and microbiological characteristics of eggshell cuticle in relation to its protective function (innate immunity) in egg-laying birds and reptiles.